IMPROVING STUDENTS' CLASSROOM BEHAVIOR BY MAXIMIZING TEACHER-STUDENT INTERACTION DURING CLASS - Purnama N.F. Lumban Batu (Celt: A Journal of Culture, English Language Teaching & Literature, 2011)
Abstract: Behavior is one thing that is really important in one's life achievement. Behaviors will develop into character that defines one's future. Further, a research of Swick shows that a student's behavior in the classroom significantly affects his/her behavior outside the classroom, as in the real world. This article is focusing on a way to improve the students' behavior in the classroom. Teachers, as students' motivator and role model, can encourage them to improve their behavior through the limited learning process at school. It not through the presented material, yet it is through the way the material is presented in the class, the interaction led by the teacher. This article is trying to apply the communication science into classical teaching-learning process related to Skinner behaviorism theory. The better the stimulus, the better the response will be. Interaction is seen as the stimulus and the students' behavior is seen as the response to it. The better the interaction, the better the behavior will be